ABOUT THE TECHNOLOGICAL PROPERTIES OF SERPENTINITES OF THE AMANDARA DEPOSIT - F. A. Badalov; D. HK. Asabaev (International Engineering Journal For Research & Development, 2021)
This article presents the results of studying the material composition and the possibility of enriching serpentinite from the Amandarinsky deposit. When Amandara serpentinite was enriched according to a combined scheme (gravity and electromagnetic separation), a 49.58% magnesium-containing product was obtained, and 72.9% was extracted. The resulting product meets the requirements of GOST 14832-96 "Refractory forsterite and forsteritochromite products. Technical conditions". Also, the article presents the results of technological research on the production of magnesium oxide serpentinite from the Amandara deposit for the magnesia refractories industry. As a result of the conducted technological studies, a magnesium–containing concentrate with a content of MgO-86.18% was obtained that meets the technical requirements GOST 1216-87 and GOST 10360-85.